PENGEMBANGAN LKPD MODEL PEMBELAJARAN LEARNING CYCLE 5E PADA MATERI FLUIDA DINAMIS UNTUK MENINGKATKAN KETERAMPILAN ARGUMENTASI ILMIAH SISWA - Asfiyah, Hilmi; Admoko, Setyo (Universitas Negeri Surabaya, 2025)
The aim of this research is to develop Student Worksheets (LKPD) using the Learning Cycle 5E learning model to train scientific argumentation skills and test the results of the validity, practicality and effectiveness of the LKPD. The Research & Development (R&D) method is applied then the model is through ADDIE (Analyze, Design, Development, Implementation, Evaluation). The research subjects were 10 class XI students. The research object is through Learning Cycle 5E learning LKPD based on Toulmin argumentation patterns. The instruments applied were LKPD validation sheets, student response questionnaires, and pretest and posttest questions. The results of this research show that the validity of the LKPD is assessed based on the appropriateness aspects of the material, work instructions, questions, scientific argumentation skills, and the 5E Learning Cycle model, getting an average percentage of 81.25%, 91.67%, 83.3%, 100%, and 100%. each with excellent criteria, valid and suitable for use. The practicality of the LKPD is based on student responses through the LKPD aspects, the 5E Learning Cycle model, motivation, Fluid Dynamics material, and scientific argumentation, obtaining an average percentage of 82%, 88%, 88.5%, 88%, respectively. and 91.5% with very strong criteria. The effectiveness of the LKPD is determined from the pre and posttest results. The test given has a high interpretation category and an average n-gain score of 0.716. So that the 5E Learning Cycle learning LKPD developed is feasible and effective in improving students' argumentation skills. Similar 5E Learning Cycle model-based LKPD can be created to improve students' argumentation skills in other physics materials